ANALISIS KELAYAKAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ON GRID MENGGUNAKAN SOFTWARE PVSYST 7.2.6 DI GEDUNG SEKOLAH - Lintang Gadis Ratu Rachellya; Teguh Utomo; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2022)
Abstrak-Pada tahun 2020-2029, kebutuhan listrik di Indonesia diproyeksikan meningkat yaitu rata-rata sebesar 6.42% (Twh) khusus dalam kebutuhan listrik (PLN, 2020). Implementasi dari sistem PLTS On Grid merupakan sistem yang memiliki pengeluaran biaya paling sedikit dikarenakan tidak diperlukannya baterai pada sistem On Grid (Kananda et. all, 2013). Salah satu pemenuhan kebutuhan listrik adalah penerapan PLTS, seperti PLTS di gedung SMA Negeri 1 Waru. Jika dilakukan tanpa koneksi on-grid, kelebihan penggunaan daya listrik PLTS tidak dapat dimanfaatkan, karena tidak dapat diekspor ke jaringan PLN. Perencanaan pemasangan sistem PLTS On Grid di SMA Negeri 1 Waru diharapkan dapat menjadi alternative solusi dalam mengurangi pembayaran dari kelistrikan pada gedung sekolah dan mengurangi penggunaan bahan bakar fosil sebagai bahan bakar utama. Adapun tujuan yang akan dicapai dalam penelitian ini dilakukan analisis performansi dan analisis ekonomis dari sistem PLTS On Grid dengan software PVSyst 7.2.6 pada SMA Negeri 1 Waru. Perancangan sistem PLTS On Grid di SMA Negeri 1 Waru Sidoarjo memiliki kapasitas sebesar 330 Wp/unit yang terdiri dari 580 unit panel surya merk JAM72-S10-330-SC pabrikan JA Solar, 6 buah inverter model MID 30KTL3-X pabrikan Growatt New Energy dengan daya nominal sebesar 30 kW/unit. Simulasi sistem PLTS dengan PVSyst 7.2.6 menghasilkan energi listrik sebesar 267,8 MWh/tahun. Perancangan sistem PLTS On Grid di SMA Negeri 1 Waru memiliki rasio performansi (PR) sebesar 76,64% untuk hasil simulasi dan 85% untuk perhitungan teori dengan investasi sebesar Rp2.332.418.971,-, Life Cycle Cost (LCC) selama 25 tahun senilai Rp2.716.836.944,, Cost of Energy (COE) senilai Rp435.404/kWh berdasarkan hasil simulasi dan Rp617,90/kWh berdasarkan perhitungan teori. Sistem PLTS di SMA Negeri 1 Waru Sidoarjo memiliki nilai Net Present Value (NPV) sebesar Rp4.773.017.432 nilai Profitability Index (PI) sebesar 3,05 dan tahun pengembalian setelah tahun ke-6,6 berdasarkan simulasi PVSyst setelah tahun ke-7 berdasarkan perhitungan manual. Pemodelan dan DED dari sistem PLTS On Grid disarankan untuk dibuat sebelum melakukan pemasangan untuk memperjelas detail ruangan, beban, dan wiring dalam gedung. Kelayakan PLTS On Grid di SMA Negeri 1 Waru Sidoarjo layak untuk dibangun dilihat dari aspek teknis dan aspek ekonomi.Kata kunci— Gedung Sekolah, PLTS, PVsyst, On-Grid, Analisa KelayakanAbstract-In 2020-2029, electricity demand in Indonesia is projected to increase by an average of 6.42% (Twh) specifically in electricity needs (PLN, 2020). The implementation of the PLTS On Grid system is a system that has the least cost because there is no need for batteries in the On Grid system (Kananda et. all, 2013). One of the potential applications of PLTS On Grid in elementary school buildings. This study conducted a performance analysis and economic analysis of the PLTS On Grid system with PVSyst 7.2.6 software at SMA Negeri 1 Waru. The design of the On Grid PLTS system at SMA Negeri 1 Waru Sidoarjo has a capacity of 330 Wp/unit consisting of 580 units of solar panel brand JAM72-S10-330-SC manufacturer JA Solar, 6 inverters model MID 30KTL3-X manufacturer Growatt New Energy with nominal power of 30 kW/unit. The PLTS system simulation with PVSyst 7.2.6 produces electrical energy of 267.8 MWh/year. The PLTS On Grid system design at SMA Negeri 1 Waru has a performance ratio (PR) of 76.64% for simulation results and 85% for theoretical calculations with an investment of Rp.2,332,418,971,-, Life Cycle Cost (LCC) for 25 years worth Rp2,716,836,944, Cost of Energy (COE) worth Rp435,404/kWh based on simulation results and Rp617.90/kWh based on theoretical calculations. The PLTS system at SMA Negeri 1 Waru Sidoarjo has a Net Present Value (NPV) of IDR 4,773,017,432, a Profitability Index (PI) value of 3.05 and the return year after the 6th year based on the PVSyst simulation after the 7th year. based on manual calculations. Modeling and DED of the PLTS On Grid system is recommended to be made prior to installation to clarify the details of the room, load, and wiring in the building. The feasibility of PLTS On Grid at SMA Negeri 1 Waru Sidoarjo is feasible to be built from the technical and economic aspects.Keywords— School Building, PLTS, PVsyst, On-Grid, Feasibility AnalysisAbstract— In 2020-2029, the electricity demand in Indonesia projected to increase by an average of 6.42% (Twh) specifically in electricity needs (PLN, 2020). Implementation of On Grid PLTS system is a system that has least expense because it is not needed battery on the On Grid system (Kananda et. all, 2013). One of fulfillment of electricity needs is the application of PLTS, such as PLTS in the SMA Negeri 1 Waru building. If done without on-grid connection, excess use of PLTS electrical power is not can be utilized, because it cannot be exported to the PLN network. Planning for the installation of the PLTS On Grid system at SMA Negeri 1 Waru is expected to be an alternative solution in reduce payments for electricity in school buildings and reduce the use of fossil fuels as fuel main. The objectives to be achieved in this research perform performance analysis and economic analysis of the system PLTS On Grid with PVSyst 7.2.6 software at SMA Negeri 1 waru. PLTS On Grid system design at SMA Negeri 1 Waru Sidoarjo has a capacity of 330 Wp/unit consisting of: 580 units of solar panels brand JAM72-S10-330-SC manufacturer JA Solar, 6 inverters MID model 30KTL3-X manufacturer Growatt New Energy with a nominal power of 30 kW/unit. System simulation PLTS with PVSyst 7.2.6 produces electrical energy of 267.8 MWh/year. PLTS On Grid system design in SMA Negeri 1 Waru has a performance ratio (PR) of 76.64% for simulation results and 85% for theoretical calculations with investment of Rp2,332,418,971,-, Life Cycle Cost (LCC) for 25 years worth IDR 2,716,836,944, Cost of Energy (COE) worth Rp435,404/kWh based on simulation results and Rp617.90/kWh based on theoretical calculations. PLTS system at SMA Negeri 1 Waru Sidoarjo has a Net Present Value (NPV) of Rp4.773.017.432 Profitability Index (PI) value of 3.05 and payback year after 6,6 year based on simulation PVSyst after 7th year based on manual calculation. Modeling and DED of the PV mini-grid system is recommended for made prior to installation to clarify details space, load, and wiring in the building. Eligibility of PLTS On The grid at SMA Negeri 1 Waru Sidoarjo is worth looking at from the technical and economic aspects. Keywords— School Building, PLTS, PVsyst, On-Grid, Analysis Appropriateness